La vengeance comme devoir: Chimène dans Le Cid de Corneille - Zsák, Helga (Verbum – Analecta Neolatina, 2001)
The essay proposes an interpretation of heroism and vengeance in Corneille's Cid with regard to the figure of Chimene. Offering a wide range of staging possibilities, the theme of female vengeance has been a recurring theme in literature since the very beginning of tragedy. Vengeace in Corneille's plays is remarkably vigorous and refers constantly to justice; characters admit their desire of vengeance and labour to fulfill it.